ANALISIS PENGARUH PANDEMI COVID-19 TERHADAP HARGA BERAS PROVINSI DI PULAU JAWA - Riska Tri Susanti (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2023)
The Covid-19 pandemic has impacted several sectors in Indonesia, but the agricultural sector continues to grow amid the weakening national economy. This study aims to analyze the fluctuations in the price of provincial rice in Java before and during Covid-19 and the factors that affect the price of provincial rice in Java using panel data. The results showed that the Covid-19 pandemic affected rice prices and resulted in fluctuations in provincial rice prices on the island of Java. Provincial rice prices in Java are also influenced by international rice prices, HPP and per capita consumption, while rice production has a negative effect on rice prices. In the short and long term, every increase in international rice prices, per capita consumption, HPP, and cases of Covid-19 will increase the price of rice, while every increase in rice production will reduce the price of provincial rice on the island of Java.